Effects of aeration on formation and localization of the acetyl coenzyme A synthetases of Saccharomyces cerevisiae. - Klein, H P (1979)
A method is shown to be effective over a wide range of enzyme ratios for the simultaneous detection of the two isoenzymes of acetyl coenzyme A synthetase [acetate:coenzyme A ligase (AMP-forming); EC 6.2.1.1] in homogenates and cellular fractions of Saccharomyces cerevisiae. When this method was used, it was found that cells grown under anaerobic conditions contained only one variety of this enzyme, designated the nonaerobic synthetase, whereas cells grown with vigorous aeration contained principally the other, aerobic, synthetase. In cells grown as standing cultures (i.e., semi-aerobically), both enzymes were present and were found mainly in the extramitochondrial material of homogenates. When anaerobic cultures were aerated, the amount of aerobic enzyme increased steadily over a 24-h period, so that at the end of this time, aerated cells contained predominantly aerobic enzyme. During this same period, the amount of nonaerobic enzyme decreased. The percentage of aerobic enzyme that sedimented with the mitochondria increased steadily during this period of aeration, so that, at the end of 24 h of aeration, essentially all of the aerobic enzyme sedimented with the mitochondria. The nonaerobic enzyme was never found in this cellular compartment.